Analysis of Climate and Environmental Risk Factors on Dengue Hemorrhagic Fever Incidence in Bogor District - Wulandari, Ririn Arminsih; Rahmawati, Tria; Asyary, Al; Nugraha, Fajar (UI Scholars Hub, 2023)
Dengue Hemorrhagic Fever (DHF) is transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes and is still becoming endemic in Bogor District. This quantitative correlation study with an ecological approach aimed to analyze how DHF incidence is influenced by climate factors, population density, Larvae Free Rate (LFR), and the area altitude factor. Secondary data were obtained from the Bogor Regency Health Office; the Central Bureau of Statistics of Bogor District; and the Meteorology, Climatology, and Geophysics Agency. In this study, the spatial analysis method was also used, but only on the area altitude factor. The study’s results showed a significant relationship between climate factors, such as air humidity at a Time Lag of 0 months (r=0.394) and the altitude factor (r=-0.350), and DHF incidence in the Bogor District from 2017 to 2022. Spatial data shows that in districts with lower altitudes, such as Cibinong, Cileungsi, and Gunung Putri, DHF incidence tends to be higher. The Bogor District Health Office, together with the community, may enhance efforts to prevent and control DHF, especially during seasonal transitions and in areas with lower altitudes. Cross-sector collaboration with the Meteorology, Climatology, and Geophysics Agency is also necessary to remain vigilant during climate fluctuations.